A data processing algorithm for multi-wavelength pyrometry-which does not need to assume the emissivity model in advance - Xing, Jian; Cui, Shuanglong; Qi, Wangui; Zhang, Fucai; Sun, Xiaogang; Sun, Weimin (Measurement : journal of the International Measurement Confederation, 2015)
•It does not assume emissivity model for multi-wavelength pyrometer.•A liner equation between emissivity and temperature at continuous time is proposed.•Simulation and experiment result is satisfactory. The problem of processing radiant temperature data in order to find true temperature and spectral emissivity in multi-wavelength pyrometry is studied using continuously measured data. The feasibility and reliability of the retrieval of true temperature and spectral emissivity based on an iteration algorithm is proposed. Such algorithm does not need to use a specific emissivity distribution vs. wavelength to find out the required quantities, but assumes a dependence of emissivity on temperature and uses data at different temperatures. Simulation and experimental results indicate that a fairly reasonable representation of true temperature and spectral emissivity distribution can be obtained using the proposed algorithm. The method has the advantages of simplicity, and suitability for on-line true temperature and spectral emissivity measurement.